2021
DOI: 10.1016/j.cels.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Multi-omic Analysis of COVID-19 Severity

Abstract: We performed RNA-seq and high-resolution mass spectrometry on 128 blood samples from COVID-19-positive and COVID-19-negative patients with diverse disease severities and outcomes. Quantified transcripts, proteins, metabolites, and lipids were associated with clinical outcomes in a curated relational database, uniquely enabling systems analysis and cross-ome correlations to molecules and patient prognoses. We mapped 219 molecular features with high significance to COVID-19 status and severity, many of which wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
641
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(721 citation statements)
references
References 96 publications
39
641
3
Order By: Relevance
“…Individuals with genetic susceptibility to a higher WHR had higher abundances of four putative viral interaction partners (LMAN2, ETFA, TBCA, and SELENOS), and lower levels of albumin, GSN, and ITIH3. Lower plasma abundances of GSN have been repeatedly associated with severity of COVID-19 7,22 . The association with plasma abundances of LMAN2 (or VIP36) was shared with the eGFR-GRS but in opposing direction (inversely).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with genetic susceptibility to a higher WHR had higher abundances of four putative viral interaction partners (LMAN2, ETFA, TBCA, and SELENOS), and lower levels of albumin, GSN, and ITIH3. Lower plasma abundances of GSN have been repeatedly associated with severity of COVID-19 7,22 . The association with plasma abundances of LMAN2 (or VIP36) was shared with the eGFR-GRS but in opposing direction (inversely).…”
Section: Resultsmentioning
confidence: 99%
“…Limitations of the study include utilizing a different method of proteomic analysis compared to others that may not be directly comparable [1]. In conclusion, 21 of 60 protein biomarkers reported in respiratory patients with COVID-19 were found to differ between women with and without PCOS, showing the necessity for validation of such biomarkers, and suggesting that more severe COVID-19 disease may occur in PCOS.…”
mentioning
confidence: 78%
“…To the Editor, Large scale multi-omics analysis has identified significant differences in the biomarkers between COVID-19 disease and control subjects [1]. These protein panels target biological processes involved in vessel damage, platelet degranulation, the coagulation cascade and the acute phase response [1], with greater protein changes dependent on the COVID-19 severity.…”
mentioning
confidence: 99%
“…Under other circumstances, case 2 may have dismissed his mild cough and sore throat as seasonal allergies, a cold, or air-quality issues in the absence of a fever and never realized he was positive for SARS-CoV-2. Currently there is an extreme paucity of information regarding the immune response over the course of infection in individuals that have very mild symptoms, as other related clinical studies have inclusion criteria that include fever or hospitalization [10,19,20,21]. Our study showed that a number of diverse immune and inflammatory pathways were activated or repressed in afebrile case 2.…”
Section: Resultsmentioning
confidence: 65%